Embedding Wound Hygiene into a proactive wound healing strategy. (1st April 2022) - Murphy, Chris; Atkin, Leanne; Vega de Ceniga, Melina; Weir, Dot; Swanson, Terry; Walker, Angela; Mrozikiewicz-Rakowska, Beata; Ciprandi, Guido; Martínez, José Luis Lázaro; Černohorská, Júlia
Abstract : Foreword. Wound Hygiene: the next stage: Since a panel published the first consensus document on Wound Hygiene in March 2020, there has been a flurry of activity in support of this newly established concept in proactive wound healing. 1 The document concluded that all wounds, particularly hard-to-heal ones, will benefit from Wound Hygiene, which should be initiated at the first referral, following a full holistic assessment to identify the wound aetiology and comorbidities, and then implemented at every dressing change until full healing occurs. 1 The consensus has since been bolstered by educational webinars; competency-based skills training and support; development of international Wound Hygiene ambassadors; a survey of 1478 respondents, published in July 2021; 2 and a case study supplement, published in January 2022, featuring a range of wound types, anatomies and underlying conditions on the improvements in wound-healing progress that can be achieved. 3 Wound Hygiene has gained its own identity and is now a term in and of itself, that encompasses a 4-step protocol of care. It is an antibiofilm approach that is increasingly being used across wound care. The results of the survey 2 were particularly encouraging for seeing how far Wound Hygiene has come, and how quickly: More than half (57.4%) had heard of the concept of Wound Hygiene Of those, 75.3% have implemented Wound Hygiene Overall, following implementation of Wound Hygiene, 80.3% of respondents reported improved healing rates. 2 However, the top three barriers identified by the survey—lack of confidence, competence and research data—show that there is more to be done to support Wound Hygiene in practice. 2 As a result, a consensus panel of international key opinion leaders convened virtually in the summer of 2021 to discuss what has been done so far, the outputs of the survey, and ideas for addressing the unmet needs identified by the results. The result is this publication, which represents an addendum to the initial consensus document, broadening support for implementation of Wound Hygiene. This document will reflect on the reasons Wound Hygiene has been successful in its first two years of implementation, reiterating its DNA: Do not wait to treat hard-to-heal wounds Use a simple 4-step approach Enable all healthcare professionals to implement and use Wound Hygiene. The document will also discuss the evolution of the Wound Hygiene concept, focusing on how and when to implement Wound Hygiene on all tissue types of hard-to-heal wounds, and proposing what these are. The panel has expanded the framework in which Wound Hygiene is used, with the ultimate objective of introducing the concept of 'embedding Wound Hygiene intro a proactive wound healing strategy.' Key inefficiencies are often observed along the journeys of people living with hard-to-heal wounds. The limited number of specialised healthcare professionals and the resulting delays in reaching them may increase the likelihood of a hard-to-heal wound developing. In a world where so much is happening so quickly that we may, at times, feel powerless to drive change, the panel wants to provide further guidance to propel the use of Wound Hygiene. The concept of Wound Hygiene is resonating, and the panel wants you to know that in whatever region you work, in whatever area of clinical practice, you are enabled to make this change. Wielding the 4-step Wound Hygiene protocol consistently is a key action every healthcare professional in every care setting can take to tackle the global wound care crisis. Wound Hygiene has taken off—now, where do we want to land? In a place where Wound Hygiene is practised on all wounds, at every stage, until healing. The panel once again recognises that the community of global healthcare providers should consider their local standards and guidelines when applying the recommendations of this document. To this end, the panel has created a flexible 3-phase framework that situates Wound Hygiene as integral to proactive wound healing. The panel hopes you will continue to implement Wound Hygiene and see the benefits it can bring to people living with wounds, as well as those who care for them.